1997
DOI: 10.1113/expphysiol.1997.sp004035
|View full text |Cite
|
Sign up to set email alerts
|

Engine and radiator: fetal and placental interactions for heat dissipation

Abstract: SUMMARYThe 'engine' of fetal metabolism generates heat (3-4 W kg-' in fetal sheep) which has to be dissipated to the maternal organism. Fetal heat may move through the amniotic/allantoic fluids to the uterine wall (conductive pathway; total conductance, 1-1 W 0C-' kg-') and with the umbilical arterial blood flow (convective pathway) to the placenta. Because resistance to heat flow is larger than zero fetal temperature exceeds maternal temperature by about 0 5°C (0.3-1°C). Probably 85 % of fetal heat is lost to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 26 publications
(49 reference statements)
3
37
0
3
Order By: Relevance
“…The experiments reported here showed that, despite robust temperature, activin A, follistatin and cytokine responses in the mother, with the exception of temperature concomitant increases in the fetal compartment were not seen. Fetal temperature did rise simultaneously with that of the mother, consistent with the idea that most heat is lost from the fetal compartment across the placenta into maternal blood (Schröder & Power 1997). However, in terms of TNF-and IL-6 concentrations in the fetus, there were no significant changes in the 24-h period following LPS treatment.…”
Section: Discussionsupporting
confidence: 64%
“…The experiments reported here showed that, despite robust temperature, activin A, follistatin and cytokine responses in the mother, with the exception of temperature concomitant increases in the fetal compartment were not seen. Fetal temperature did rise simultaneously with that of the mother, consistent with the idea that most heat is lost from the fetal compartment across the placenta into maternal blood (Schröder & Power 1997). However, in terms of TNF-and IL-6 concentrations in the fetus, there were no significant changes in the 24-h period following LPS treatment.…”
Section: Discussionsupporting
confidence: 64%
“…The efficiency of exchange can be predicted by interdigitation and the placental shape. In labyrinthine placentae, counter-current flow with cross-current components is the most common arrangement Miglino et al 2004), with counter-current flow considered the most effective for maternofetal exchange (Faber et al 1992); whereas the predominant cross-current flow in villous placentae are buttressed by the ratio of maternofetal blood flow (Schroder and Power 1997; also see Moll 1972;Benirschke and Kaufmann 2000, pp. 35-38).…”
Section: Diffusion and Exchangementioning
confidence: 97%
“…Because the heat from thermo-generating organelles diffuses rapidly throughout the cell and beyond [28], it is ideal if the sensor can be targeted directly to the organelles where the heat is generated. In these points of view, each category of technique has its own unique properties, and the characteristics and advantages/disadvantages of these methods are summarized in Table 2.…”
Section: Comparison Of Techniquesmentioning
confidence: 99%